PERSEPSI GURU TERHADAP PERSIAPAN DIRI DALAM MENGHADAPI KURIKULUM MERDEKA DI SD NEGERI 13/1 MUARA BULIAN - Rosidah; Yantoro; Suci Hayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to (1) describe teachers’ perceptions of self-preparation in facing the Merdeka Curriculum at SD Negeri 13/1 Muara Bulian, and (2) identify the factors influencing teachers' self-preparation. This descriptive qualitative research involved interviews and documentation for data collection. The subjects were the principal, homeroom teachers, and subject teachers totaling four participants. The results show that teachers have a positive perception of the importance of self-preparation. Teachers have begun preparing by seeking information about the Merdeka Curriculum through the internet and the Merdeka Mengajar platform. They also attend school-facilitated seminars, engage in peer discussions, and improve their technological skills for teaching and assessment purposes. Influencing factors in teacher preparation include leadership, motivation to become engaging educators, student characteristics, relevant curriculum development, innovative teaching methods, professional growth, and collaboration with parents. Based on the findings, it is recommended that teachers continue to strengthen their understanding of the Merdeka Curriculum using available resources, and schools are encouraged to support teacher readiness through appropriate facilities and training opportunities.